The effects of coping interventions on ability to perform under pressure - Kent, S.; Devonport, T. J.; Lane, A. M.; Nicholls, W.; Friesen, A. P. (Journal of Sports Science & Medicine, 2018)
The ability to perform under pressure is necessary to achieve goals in various domains of life. We conducted a systematic review to synthesise findings from applied studies that focus on interventions developed to enhance an individual`s ability to cope under performance pressure. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, a comprehensive search of five electronic databases was conducted. This yielded 66,618 records, of which 23 peer review papers met inclusion criteria of containing an intervention that targeted coping skills for performing under pressure. Using the Standard Quality Assessment for evaluation of primary research papers (Kmet et al., 2004) to assess quality, included studies performed well on reporting research objectives, research design, and statistical procedures. Sixteen studies showed poor quality in controlling for potentially confounding factors and small sample sizes. A narrative aggregate synthesis identified intervention studies that provided an educational focus (n = 9), consultancy sessions (n = 6), simulation training (n = 5) and emotion regulation strategies (n = 3). Findings highlight a need to; 1) establish a contextualized pressure task which will generate high levels of ecological validity for participants. Having established a suitable pressure task, 2) research should assess the effects of pressure by evaluating conscious and nonconscious effects and associated coping mechanisms, which should inform the subsequent development of interventions, and 3) assess interventions to enhance understanding of the ways in which they improve coping with pressure, or may fail, and the mechanisms which may explain these outcomes.